Analisis Produksi Ayam Petelur Fase Layer pada CV Surya Multi Farm di Kabupaten Bulukumba Sulawesi Selatan: Production Analysis of Layer Phase of Laying Hens at CV Surya Multi Farm in Bulukumba Regency, South Sulawesi - Anas Qurniawan; Suci Ananda; a. May Zohra; Ayu Lestari; Darmawan Risal; Nuryahya Abdullah; Ahmad Firman Ashari; Munawir; Nurfaisah Baharuddin (Universitas Islam Negeri Alauddin Makassar, 2023)
Laying hens are one of the poultry that is widely cultivated by Indonesian people and is quite developed in South Sulawesi, especially in Bulukumba Regency. Laying hen farming business is a business that can generate fast capital turnover, besides that laying hen farming business is still very vulnerable and prices are still fluctuating. The purpose of this study was to determine the production analysis of laying hens in Bulukumba Regency, South Sulawesi. There are two data collected, namely primary data and secondary data. Primary data come from interviews and observations, while secondary data comes from maintenance management SOP/manual book, then analyzed using descriptive method. The conclusion from the results of the analysis of the layer phase production of laying hens in Bulukumba Regency, South Sulawesi can be seen in the maintenance of layer phase laying hens using a battery cage type and the cage model used is an open house cage and where the increase and decrease in egg production is caused by the provision of inefficient feed, namely when mixing feed should be done 3 minutes after the last ingredient entered the mixer, but sometimes the workers only use 30 seconds-1.5 minutes which causes an inhomogeneous ration. Health management is carried out by injecting the Medivac ND-IB vaccine to prevent ND and IB diseases once every 1.5 months, the administration is carried out by injection. The type of vaccine used is the active ND-IB vaccine, which is activated via 500 ml of adesta solution which must be used up within 2 hours for 1000 chickens with a dose of 0.5 ml/head per head, while for DOC it is 0.2 ml/head.